Analaysis of a large-scale database for energy performance modeling of existing buildings - Kim, Hye Gi; Jae Eun, Sung; Sun Sook, Kim (ASHRAE and IBPSA-USA Building Simulation Conference, 2018)
As the importance of energy efficiency improvement and management of existing buildings increases, the importance of energy simulation and energy use evaluation of existing buildings is also increasing. However, unlike new building, the level of available information that can be entered into the simulation varies from building to building. Therefore, in various countries were developing and providing a reference model of the existing buildings for evaluating energy performance by using the available information or the standards according to completion year of the building. However, information that can not be gathered is usually input assumed value by the case study or previous studies. The ultimate goal of this study is to replace the assumed values of variables with more accurate and reliable information by calibrating the model output with measurement data. And, it is to provide which not a single reference building but a reference building pakage that can be evaluated to reflect various building characteristics across the country. This study is a basic study for this purpose, to develop a reference building pakage for the national-wide offices according to the existing reference building development method and to present the calibration direction by comparing it with the available information of the existing building.
Keywords: Building characteristics; Building development; Energy efficiency improvements; Energy performance; Energy simulation; Large-scale database; Measurement data; Reference modeling